On the Beneficiary Inscriptions In the South of the Province of Moesia Superior (The examples from Kosovo and Metohija) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper presents data on consular beneficiary stations in Kosovo and Metohija (the south of the province of Gornja Mezija). It is about beneficiary inscriptions which were found near roads which intersected Kosovo and Metohija from the north to south areas (Narona–Scupi) and from the southwest to northeast areas (Lissus–Naissus). Consular beneficiries were legionaries legio VII Claudiae and legio IV Flaviae in these stations. A critical review of the function and the position of consular beneficiaries, who were the guardians of public safety, is given as well.
Keywords: beneficiaries; inscriptions; legions; Moesia Superior; Kosovo and Metohija